2014
DOI: 10.2190/om.70.2.a
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth and Stigma: The Spoiling and Repair of Multiple Social Identities

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThis study investigated mothers' experiences surrounding stillbirth in the UK, their memory making and sharing opportunities, and the effect these opportunities had on them. Qualitative data were generated from free text responses to open-ended questions. Thematic content analysis revealed that "stigma" was experienced by most women and Goffman's (1963) work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 67 publications
3
33
0
1
Order By: Relevance
“…For example, maternal trauma, such the previous stillbirth of a child or an atypically‐developing child, was identified as a factor influencing mothers' decisions whether to attend FTPG or not. This finding is consonant with theories indicating that parents of a stillborn child might avoid social support networks for subsequent children in order to avoid awkward conversations with others in which they acknowledge their bereavement (Brierley‐Jones, Crawley, Lomax, & Ayers, ), or alternately to avoid the guilt of not acknowleding their deceased child (Üstündag‐Budak et al, ). Similarly, avoidance of potential social stigma is also a recognized parental response when a child has a disability (Segal, Mandich, Cook, & Polatajko, ).…”
Section: Discussionsupporting
confidence: 82%
“…For example, maternal trauma, such the previous stillbirth of a child or an atypically‐developing child, was identified as a factor influencing mothers' decisions whether to attend FTPG or not. This finding is consonant with theories indicating that parents of a stillborn child might avoid social support networks for subsequent children in order to avoid awkward conversations with others in which they acknowledge their bereavement (Brierley‐Jones, Crawley, Lomax, & Ayers, ), or alternately to avoid the guilt of not acknowleding their deceased child (Üstündag‐Budak et al, ). Similarly, avoidance of potential social stigma is also a recognized parental response when a child has a disability (Segal, Mandich, Cook, & Polatajko, ).…”
Section: Discussionsupporting
confidence: 82%
“…Finally, the present study highlights that the loss of a child during or prior to birth is no less painful than the loss of a child during the first year of life. Several parents who have gone through a stillbirth report feeling neglected and ignored by hospital staff, as though their loss is not real [47]. The findings of the present study emphasize that there are no empirical grounds for treating parents who go through a stillbirth any differently from parents who have lost a child after birth.…”
Section: Discussionmentioning
confidence: 53%
“…The importance of creating and sharing lasting memories has been shown previously . Crawley et al found that a high degree of memory sharing after the loss of a child was associated with fewer PTSD symptoms in the mothers. Women should therefore be encouraged to not only create lasting memories but also share them with their partner, family, and friends.…”
Section: Discussionmentioning
confidence: 83%